The determinants of corporate cash holding in manufacturing sector in Malaysia / Nor Zaidah Kamis - Kamis, Nor Zaidah (2007)
This study presents and the determinants optimum corporate cash holding in manufacturing sector in Malaysia. It is important to hold appropriate cash because (l) Cash holdings reduce the likelihood of financial distress (2) cash holdings allow the pursuance of the optimal investment policy even when financial constraints are met. And (3) cash holdings contribute to minimize the transaction costs of raising external funds or do not have to liquidate existing assets to make payments. Secondary data being used for this study are cash to total assets, total leverage, market to book value and cash flow to assets as a proxy to cash holding, total debt to the company, opportunities growth and profitability. This study concentrated on the 50 manufacturing sector companies listed in Main Board of Bursa Malaysia. This study is conducted by using SPSS in order to find the data is significant or not through regression. Based on the analysis, growth opportunities and leverage is significant. There findings obtained have indicated that there is a positive relationship between cash holding and growth opportunities. This is because when firm high growth opportunities, they tend to accumulates more cash. While, cash holding and leverage has negative relationship.